Analisis Efektivitas Pola Seleksi Penerimaan Mahasiswa Terhadap Tingkat Registrasi Ulang di Universitas Islam Indonesia - Wibowo, Nuki Ari; Paputungan, Irving Vitra (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
New student admission is a strategic process in higher education management because its success is determined not only by the number of students accepted, but also by the institution's ability to convert prospective students into re-registered students. This study aims to evaluate the effectiveness of the student admission selection pattern at the Islamic University of Indonesia for the 2023/2024–2025/2026 academic year based on the ability of each pattern to produce registered students. The study uses a quantitative approach with a descriptive evaluative method based on institutional data from the UII Monitor PMB system. The evaluation was conducted using conversion rate, enrollment yield, and withdrawal rate indicators. Data analysis includes descriptive statistics to describe admission performance, trend analysis to observe changes between periods, and Chi-Square and standardized residual tests to identify differences in the contribution of selection patterns to re-registration. The results show that the Cyber ​​pattern has the highest conversion rate of 27.79%, followed by CBT at 16.66%, PSB at 4.20%, and International at 3.38%. The chi-square test showed a significant difference between the selection patterns (χ² = 5029.271; p-value < 0.001). This finding suggests that data-based evaluation of selection patterns can inform decision-making in optimizing new student admission strategies.